NOVEL CHARLOTTE KARYA DAVID FOENKINOS: SEBUAH NARASI TENTANG DISKRIMINASI, RASISME, DAN HOLOCAUST - Tania Intan (POETIKA, 2017)
The Nazi ruling since 1933 made no secret of his dislike of Jews. Adolf Hitler even declared that "rational antisemitism must lead to a system of legal opposition, the ultimate goal of wiping out all Jews" (Mein Kampf, 1925: 27). He also developed the idea that Jews are the evil race that dominates the world. Nazi anti-Semitism is instilled in religious situations and in a political context. Then, the Nazis added a further dimension, racial anti-semitism. With the logic that Jews are not religious but racial communities, the Nazis launched various aggressions in the form of discriminatory, racist, and Holocaust. This dark phenomenon in human history is revealed in Charlotte's novel by David Foenkinos, a French writer who often receives literary awards. The discussion will be conducted by descriptive analysis method through structural approach which includes assessment of character, background, and point of view. Key words : Discrimination, Racism, Holocaust, Charlotte